Development of ammonium perchlorate based solid propellant - Ahmad Hakimi, Abdul Nasir (2013)
There are a lot of development and study of ammonium perchlorate (AP) based solid propellant are already existing in the world. However, there are no detail data and information on the low burning rate AP based solid propellant. This thesis discusses the study of development AP based solid propellant. The objective of the study is to develop low burning rate AP based solid propellant including the selection of a propellant formulation, preparation and development of the propellant, and propellant burning rate experiments with the strand burner at atmospheric pressure. Together with the literature study and theoretical performance, five sets of different mixture were chosen based on their efficiency of propellant mixture. The propellant was a mixture of AP as an oxidizer, aluminum (Al) as fuel and hydroxy-terminated polybutadiene (HTPB) as a binder. For each mixture, HTPB was set at 15% and cured with isophorone diisocyanate (IPDI) (9.33% per weight of HTPB). By changing the AP and Al, the effect of oxidizer- fuel (O/F) ratio on the whole propellant can be determined. The lowest value of the testing obtained are propellant f80, that is 1.47mm/sec with O/F ratio 16.0. The study found, increased ratio O/F will affect to the combustion rate reduction factors of propellant.